(untitled) (AYUSHDHARA, 2019)
Ayurveda science follows the principle that when there is accumulation of morbid Dosha it needs to be expelled out from the nearest route which is also known as Shodhana therapy. Vamana (therapeutic emesis) is a therapeutic procedure in which Apakva (unripen stage) Pitta or Kapha Doshas are expelled out through oral route. Madanphala known as Randia Dumetorum (Reitz) Poir belongs to Rubiacea family is most commonly used drug for Vamana and is considered as best one because of its Anapayitatva qualities means having very less complications and is safer to use. It is considered as Agrya Dravya (best drug) for Vamana, Asthapana and Anuvasana. It possesses qualities like Madhura Tikata or Katu Tikta Rasa (taste), Laghu Rukhsa qualities, Katu Vipaka (post digestive effect) and Ushna Virya (potency). It performs various actions like Vamana, Lekhana, Jvaraghana, Shothaghana, Jvaraghana, Shothaghana. It has been indicated in Pratishyaya, Shleshama Jvara, Vidhradhi, Gulma, Shosha, Shotha, Anaha, Vrana, Kushtha, Kaphaj Hridroga, Pakvashaya shodhana and Kapha Vata diseases. Through various sources synonyms, qualities, actions, indications, posology, toxicities and its treatment has been collected. This information will help for further research to validate the classical uses of Madanphala.